The Jubilee Line Extension stations celebration of architecture and engineering : an insight into the architectural aspects of the JLE stations and the challenging environments that the engineers worked within during their construction : compiled from presentations made at a special British Cement Association/Institution of Civil Engineers seminar, 10 November 1999, London. (Thomas Telford, 1999)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a joint BCA/ICE seminar held on 10 November 1999.